The Transformation of Classical Nahwu into Modern Form in The Perspective of Tamam Hassan - Nurmasyitah, Putri; Wahyudi, Jarot; Pribadi, Mohammad (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2025)
This study explores the evolution of nahwu (Arabic grammar) from a classical to a modern paradigm through a comparative analysis of the word classification systems developed by Imam Sibawaihi and Tamam Hassan. Sibawaihi’s traditional model, which categorizes words into three core types ism, fi‘l, and harf is grounded in formal grammatical structure. While foundational to Arabic grammar for centuries, this system tends to be overly broad and less responsive to the complexities of contemporary language use. In contrast, Tamam Hassan, influenced by modern functional linguistics, proposed a more nuanced system comprising seven categories: ism, fi‘l, shifah, dhamir, khalifah, dzarf, and adat. His classification emphasizes the functional roles of words in context, allowing for a more detailed analysis of meaning, expression, and interaction. Employing a qualitative descriptive-comparative method, this study analyzes both models through Halliday’s metafunctional framework ideational, interpersonal, and textual. The findings reveal that Hassan’s system offers distinct advantages in accounting for linguistic variation in contemporary contexts such as social media, journalistic writing, and business communication. Ultimately, Hassan’s functional model revitalizes nahwu as a dynamic and context-sensitive discipline that is better aligned with the communicative needs of modern Arabic users.